Examination of type material of two species of Litomosoides (Filarioidea : Onchocercidae), parasites from bats ; taxonomic consequences - Bain O.; Guerrero R.; Rodriguez B.; Babayan S.; Jouvenet N. (Parasite, 2003)
Type material of Litomosoides hamletti Sandground, 1934 from Glossophaga soricina soricina in Brazil and L. penai Jiménez- Quirós & Arroyo, 1 960 from Carollia perspicillata azteca in Costa Rica, was examined. The morphology of the spicules shows that these species belong to the carinii group. Their synonymy with L. guiterasi Pérez Vigueras, 1934, from Artibeus jamaicensis yucatanicus in Cuba, does not appear justified because they are distinct in several characters (body length, width of female, size and shape of buccal cavity and capsule, shape of right spicule). L. hamletti is a valid species; L. penai is closely related to it and is considered to be a sub-species, L. hamletti penai Jiménez-Quirós & Arroyo, 1960: The material recovered from Glossophaga spp., previously assigned to L guiterasi by several authors, is identified as L. h. hamletti. L. guiterasi appears to be closely related to L chandleri Esslinger, 1973; L. chitwoodi n. sp. (= Litomosoides sp. Chitwood, 1938) seems close to these species; all three are parasites of Artibeus spp.